KORELASI MOTIVASI BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 43 MERANGIN - Hestin Nurul Hikmah; Ferinaldi; Sugeng Riyadi (Matedukasia, 2024)
The purpose of this research is to determine the correlation between learning motivation and mathematical concept comprehension. The method used in this research is quantitative with a correlational research design. The sample for this research consists of 51 randomly selected 8th-grade students from SMP Negeri 43 Merangin. Data collection was done by distributing a learning motivation questionnaire and a set of 4 essay questions to assess mathematical concept comprehension. Data analysis for this research includes descriptive statistical analysis and correlation analysis. The research results indicate that there is a correlation between learning motivation and mathematical concept comprehension among 8th-grade students at SMP Negeri 43 Merangin.